2024
DOI: 10.7759/cureus.54881
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Diverticula Supplied by the Anomalistic Branch of the Right Coronary Artery

Hidekazu Takeuchi

Abstract: We have reported several cases of pulmonary vein thrombosis in elderly individuals with or without chest pain; pulmonary vein thrombosis is common in aged individuals and should be evaluated further. However, the properties and roles of pulmonary vein thrombi (PVTs) have not been determined. During infection, neutrophil extracellular traps (NETs) are produced to kill pathogens, and arterial thrombi (ATs) are produced in pulmonary veins to prevent pathogens from spreading to all organs. We reported that fine PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We have previously reported that when LA thrombi from RIPV thrombi attach to the anterosuperior wall of the LA, the LA thrombi look much whiter and do not move periodically with the heartbeats [4,6]. However, then 80-MDCT did not detect expanded LA thrombi [4,6]. Why such differences are observed is unclear.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We have previously reported that when LA thrombi from RIPV thrombi attach to the anterosuperior wall of the LA, the LA thrombi look much whiter and do not move periodically with the heartbeats [4,6]. However, then 80-MDCT did not detect expanded LA thrombi [4,6]. Why such differences are observed is unclear.…”
Section: Discussionmentioning
confidence: 95%
“…In many cases, each patient had thrombi in several pulmonary veins, and these thrombi formed a network of PVTs in the left atrium (LA) [3]. We reported several cases of PVTs in older individuals with or without chest pain [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PVTs have the potential to be the source of retrieved thrombi, indicating that PVTs can cause ischemic stroke (IS) and acute myocardial infarction (AMI) [5,6]. We have reported several cases of PVTs using cardiac computed tomography (CT) and transesophageal echocardiography (TEE) [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%